Kemampuan Membaca Memahami Teks Bahasa Jerman - Ervi Ervi; Muh Anwar (Universitas Negeri Makassar, 2023)
Abstract. The purpose of this study was to obtain data and information about the ability to read and understand German language texts for class XI students of Makassar. This research is a descriptive research and data collection is used to test the ability to read and understand German texts. Data analysis used percentage technique. The population in this study were 100 students of class XI Social Sciences at SMA Negeri 3 Makassar, and the sample was class XI IPS 3, totaling 31 people who were determined by random sampling. The results of this study indicate that the level of reading comprehension ability of students’ German language texts. Class XI IPS 3 SMA Negeri 3 Makassar is enough 70%.Keyword: Reading skills, German